Reconstructing The Role Of Parents and Teachers In Islamic Education - Ana Fergina; Syarifuddin Ondeng; Saprin (IJGIE (International Journal of Graduate of Islamic Education), 2024)
This research aims to explain the importance of reconstructing the roles of parents and teachers in Islamic education. It is a descriptive study utilizing a literature review. The roles of parents and teachers in Islamic education need to be reconstructed because children are growing up in a different era from their parents and teachers. The millennial era, characterized by technology reliance, makes children quickly adapt to their surroundings. However, to protect children from the negative influences of the times, parents and teachers must possess competencies beyond merely educating and teaching in the real world but also guiding them in the virtual world. Therefore, Islamic education for children must be preserved, and parents and teachers must continue to be educators, guides, motivators, and role models for their children so that they can compete in their time while maintaining good moral character according to Islamic teachings.